Trauma, resilience, and math learning: African American students’ perspectives on adverse childhood experiences - Nwogbo, Antonia (American Journal of STEM Education, 2025)
This qualitative study investigates how Adverse Childhood Experiences (ACEs) shape the mathematical learning experiences of ten African American community college students from urban backgrounds. While ACEs are known to influence mental health and cognitive development, their specific impact on mathematics learning remains underexplored—especially among historically marginalized populations. Guided by Contemporary Trauma Theory, the Theory of Allostasis, and the Ecological Assets framework, this study reveals how trauma manifests in executive functioning challenges, affective responses, and learning behaviors. Despite these obstacles, students demonstrated significant resilience, supported by ecological assets such as mentoring, supportive relationships, and culturally responsive environments. Findings underscore the importance of trauma-informed, equity-focused approaches in STEM education and call for a reexamination of deficit narratives around mathematics achievement.